Trends in Global Disarmament Treaties. (11th December 2020) - Casey-Maslen, Stuart; Vestner, Tobias
Abstract: Since the adoption of the UN Charter, states have concluded numerous international disarmament treaties. What are their core features, and are there any trends in their design? This article discusses the five global disarmament treaties, namely the 1971 Biological Weapons Convention, the 1992 Chemical Weapons Convention, the 1997 Anti-Personnel Mine Ban Convention, the 2008 Convention on Cluster Munitions and the 2017 Treaty on the Prohibition of Nuclear Weapons. It first considers how a broad set of prohibitions of activities with respect to specific weapons has evolved over time. Then, it analyses the treaties' implementation and compliance support mechanisms as well as their procedural aspects regarding entry into force and withdrawal. This article finds that a pattern has developed over the last two decades to outlaw all and any use of weapons by disarmament treaty, without first instituting a prohibition on their use under international humanitarian law (IHL). It also finds that reporting obligations, meetings of States Parties and treaty-related institutions are generally created, either directly by treaty or by subsequent state party decisions. Finally, there is a tendency to make the treaty's entry into force easier, and the withdrawal more difficult. It is argued that these trends arise from states' attempt to establish more easily disarmament treaties, design more robust disarmament treaties and more effectively protect civilians. The article concludes by reflecting whether these trends form the basis of a new branch of international law—international disarmament law—and discusses them in the context of emerging weapons and technologies.